INTERPRETATION OF HYPERFINE SHIFT PATTERNS IN FERRICYTOCHROME-B(5) IN TERMS OF ANGULAR POSITION OF THE HEME - A SENSITIVE PROBE FOR PERIPHERAL HEME PROTEIN INTERACTIONS - LEE, KB; LAMAR, GN; MANSFIELD, KE; SMITH, KM; POCHAPSKY, TC; SLIGAR, SG (ELSEVIER SCIENCE BV, 1993)
The H-1-NMR hyperfine shift pattern of the heme in a variety of low-spin ferricytochromes b5 has been analyzed in terms of the angular position of the prosthetic group within a structurally and magnetically-conserved protein matrix. A simple model is presented in which the changes in the spread of the predominantly contact shifted methyl and predominantly dipolar shifted meso-H signals of the heme, as well as shift trends for individual signals, provide sensitive indicators of the orientation of the heme relative to the orbital hole (singly-occupied d orbital), which in turn is related to the rhombic magnetic axes. The invariance of the axial His and non-coordinated residue hyperfine shifts show that it is the heme within a relatively rigid protein matrix, rather than the magnetic coordinate system, which is displaced angularly about the heme normal in order to accommodate variations in the polypeptide, orientation of the heme about the alpha,gamma-meso axis, and length of heme carboxylate chains. Native heme shows increased counterclockwise rotation about the heme normal in the order rat --> beef --> chicken ferricytochrome b5, which is attributed largely to increased bulk of a variable sequence hydrophobic cluster consisting of residues 23, 25 and 32. The two alternate heme orientations about the alpha,gamma-meso axis are shown to also differ by rotation about the heme normal. A semiquantitative estimate of the degree of angular accommodation based on the spread of the meso-H rhombic dipolar shifts indicate rotations of 2-10-degrees. Possible functional consequences of such angular accommodation in relation to the role of these proteins in electron transfer are discussed.
Keywords: PROSTHETIC GROUP RECOGNITION; NUCLEAR MAGNETIC-RESONANCE; CYTOCHROME-C; ELECTRON-TRANSFER; SPERM WHALE; PSEUDOCONTACT SHIFTS; CYANIDE COMPLEXES; PROTON-EXCHANGE; HUMAN MYOGLOBIN; H-1-NMR